Consumer demand for urban forest ecosystem services and disservices: Examining trade-offs using choice experiments and best-worst scaling (2018)
Many studies value urban ecosystem service benefits using residents’ willingness to pay and supply-side analyses of ecosystem attributes. But, few studies account for consumer demand and ecosystem disservices. To address this gap we surveyed 1052 homeowners eliciting consumer demand for key urban forest ecosystem attributes and service-disservice levels in both their properties and surrounding neighborhood. We use an approach integrating focus group, field data, and surveys to identify consumer preferences and trade-offs between urban forest ecosystem structure-functional attributes and their level of services and disservices. This method, called best worst choice, produces more estimates of utility while reducing the likelihood of introducing biases associated with human cognitive tendencies. Results indicate that consumer choices for property value were highest followed by tree condition, a structural proxy for minimizing disservices, and tree shade, a functional proxy for temperature regulation. We also found evidence of trade-offs in demand for different ecosystem services, significant scale effects, and that willingness to pay for ecosystem disservices was negative. Findings suggest that management, and studies that value and map ecosystem services, using fixed scales should account for end-user demand and functional traits, as consumers can discern trade-offs in benefits and disservices across different cognitive and spatial scales. © 2017 Elsevier B.V.